DOMINANT EFFECT BETWEEN COMPENSATION, LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE IMPROVEMENT - Fithriana, Noora; Adi, Agung Nugroho (Jurnal Aplikasi Manajemen, 2017)
The performance of employees is closely related to compensation (total cash), organizational culture, and leadership. This research aims to identify the independent variables: compensation (X1), leadership (X2), and organizational culture (X3) by dependent variable of performance (Y). The result of multiple regression analysis had identified that organizational culture dominantly influenced the employee performance in the Integrated Office of Malang City.